Addition of zinc and selenium to papaya extract enhances its efficiency of wound healing - Akram, Haris B.; Nuzwua, Dinie; Yusuf, Mohammed; Rahman, Mohammad Tariqur (Wiley-Blackwell Publishing, INC, 2009)
Wounds due to injuries for various reasons and for the diabetic patients havebeen a major public health concern. In search for a wound healing agent of herbal origin, earlier we have reported the efficiency of the green (unripe) Carica papaya extracts (GPE) for wound healing [1]. Here we report that addition of zinc and selenium with GPE results in further improvement of wound healing efficiency. Induced epidermal wounds on mouse (n=5–7 for each group) were topically treated with GPE, prepared either in PBS or water as solvent. Zinc was added at concentration of 100Mand 200Mwhile selenium was added at a concentration of 2.5Mand 5M. Zinc addition at 100Mwas resulted in highest rate of wound healing compared to the addition of either 200M of Zn or Se (either at 2.5M or 5 M). During the first phase (0–4 days) of wound healing addition of 100M Zn to GPE resulted in about 50% reduction of the initial wound size (5mm diameter). During the same period of time, treatment with the GPE in combination with either 200M of Zn or 5M of Se as well as solcoseryl (commercially available wound healing agent) resulted in not more than 30% reduction of the initial wound size. Unlike solcoseryl treatment 100M of Zn added GPE did not show any sign of inflammation. Compared to the other groups of mice, complete hair growth on the area of regenerated skin was also significantly rapid in the mice treated with 100M of Zn.